Optimizing Total Phenolic and Oleuropein of Chinese Olive (Olea europaea) Leaves for Enhancement of the Phenols Content and Antioxidant Activity - Bixia Wang; Shian Shen; Jipeng Qu; Zhou Xu; Shiling Feng; Tao Chen; Chunbang Ding (Agronomy, 2021)
China, as a contrary climate to the Mediterranean-climate region, is massive in planting olive (Olea europaea) cultivation as an important oil crop. Nonetheless, Chinese olive leaves have received little attention and there is little information about the phenols content. Therefore, in this study, a multiple-response optimization was performed to maximize the total phenolic and oleuropein content (TPC and OEC) by ultrasound-assisted extraction, and the aged and young leaves prepared from six Chinese cultivars from January to December were investigated concerning seven main phenolic composition. Under optimal conditions (power 260 W, time 10 min, liquid-solid ratio 30 mL/g, and 50% ethanol), the highest TPC (197.32 mg/g DM) and OEC (74.68 mg/g DM) were obtained. Findings revealed that the optimal olive leaves for phenolic compounds were the young leaves in spring and winter, being oleuropein and luteolin-4′-O-glucoside present in higher level, and the “Koroneiki” and “Jiufeng” cultivars were relatively stable. Furthermore, antioxidant potential of the phenol extract and oleuropein was also evaluated based on the reducing power and scavenging effect on 1,1-diphenyl-2-picrylhydrazyl (DPPH)and superoxide radical assays, and a higher antioxidant effect of oleuropein was observed compared to the phenol extract. In addition, oleuropein showed anticancer activity against HeLa cells, with a minimum inhibitory concentration (EC50) value of 0.19 mg/mL at 48 h. These findings revealed an attractive source of biological substances for further development and utilization of Chinese olive leaves.